Identification of Maxillofacial Problems in Extraoral Photographs by Panel Members: A Pilot Study - Yağmur Kılıçaslan; Türkan Sezen Erhamza; Ferabi Erhan Özdiler (Galenos Yayinevi, 2019)
Objective:The aim of this pilot study was to evaluate the effectiveness of the profile and frontal photographs in determining sagittal maxillofacial problems by the panel members created from different professional groups.Methods:Frontal and profile photographs of four individuals with skeletal Class I, Class II Division 1, Class II Division 2, and Class III malocclusion were assessed by panel members. A total of 42 panel members from 7 different professions participated in the study. Panel members were asked to choose one of the frontal or profile photographs to be used in determining the maxillofacial problem. Mann-Whitney U test, Kruskal-Wallis test, and Fisher's exact test were applied to evaluate the difference between the panelists.Results:Of the 42 panel members, 16% selected frontal photographs, and 84% selected profile photographs. There were no statistically significant differences between seven panels with regard to photography selection (p>0.05). When all panel members were compared with regard to gender, 17.9% of the frontal photographs and 82.1% of the profile photographs were selected by females, whereas 15.4% of the frontal photographs and 84.6% of the profile photographs were chosen by males. There was no statistically significant difference between males and females (p>0.05).Conclusion:It was found that the profile photograph was more preferred and informative in determining the sagittal maxillofacial problem.